2012
DOI: 10.1007/s12035-012-8284-7
|View full text |Cite
|
Sign up to set email alerts
|

BDNF and DYRK1A Are Variable and Inversely Correlated in Lymphoblastoid Cell Lines from Down Syndrome Patients

Abstract: Down syndrome or trisomy 21 is the most common genetic disorder leading to mental retardation. One feature is impaired short- and long-term spatial memory, which has been linked to altered brain-derived neurotrophic factor (BDNF) levels. Mouse models of Down syndrome have been used to assess neurotrophin levels, and reduced BDNF has been demonstrated in brains of adult transgenic mice overexpressing Dyrk1a, a candidate gene for Down syndrome phenotypes. Given the link between DYRK1A overexpression and BDNF red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
1
18
1
Order By: Relevance
“…Other reports have shown increased expression of cFOS and EGR1 in response to oxidative stress (45,46) and suggested that this induction is protective (47). If elevated levels of IEG proteins in Tc1 mice are a protective response to elevated levels of oxidative stress, they may be a compensatory response in Tc1 (and DS) and not an abnormality that would be beneficial to alter directly with pharmacotherapies.In contrast to observations in human DS lymphoblastoid cell lines (48), no correlations were observed in Tc1 brain regions between the levels of DYRK1A and BDNF. Indeed, BDNF levels were decreased and only in Tc1 cortex.…”
Section: Discussionmentioning
confidence: 70%
“…Other reports have shown increased expression of cFOS and EGR1 in response to oxidative stress (45,46) and suggested that this induction is protective (47). If elevated levels of IEG proteins in Tc1 mice are a protective response to elevated levels of oxidative stress, they may be a compensatory response in Tc1 (and DS) and not an abnormality that would be beneficial to alter directly with pharmacotherapies.In contrast to observations in human DS lymphoblastoid cell lines (48), no correlations were observed in Tc1 brain regions between the levels of DYRK1A and BDNF. Indeed, BDNF levels were decreased and only in Tc1 cortex.…”
Section: Discussionmentioning
confidence: 70%
“…These immortalized cells, which are grown in cell culture medium, have no direct relations with the tissues or cells producing DYRK1A in plasma. Although it is too early to differentiate between a genetic or epigenetic mechanism, these results together with the observation that DYRK1A levels vary among the population, 12 suggest that DYRK1A decrease might be a novel risk factor for AD.…”
Section: Discussionmentioning
confidence: 93%
“…11,12 Proteins separated by SDS–PAGE were transferred to a nitrocellulose membrane (ProtanR) using a slot blot apparatus (Proteigene, St Marcel, France). Membranes were saturated by incubation in 5% w/v nonfat milk powder in Tris–saline buffer (1.5 m M Tris base, pH 8; 5 m M NaCl; 0.1% Tween-20) and incubated overnight at 4 °C with antibodies against DYRK1A (1/250; Abnova Corporation, Taipei, Taiwan; H00001859-M01).…”
Section: Methodsmentioning
confidence: 99%
“…XBP1s has also been shown to regulate the expression of ADAM10, an α-secretase that cleaves β-amyloid and generates non-toxic species [67]. These reports suggest that XBP1s overexpression observed in DS models might be an attempt of DS cells to either protect themselves against toxic β-amyloid species produced as a result of APP overexpression [68], or as a protection against the lack of neurotrophic factors, also observed in DS models [69, 70]. A similar induction of UPR has also been observed in cataracts [71], epilepsy [72], hypothyroidism [73] and diabetes [74].…”
Section: Discussionmentioning
confidence: 99%